Review of the scorpionfly genus Dicerapanorpa Zhong & Hua (Mecoptera: Panorpidae), with descriptions of two new species - Gui-Lin Hu; Bao-Zhen Hua (European Journal of Taxonomy, 2020)
The current knowledge of the scorpionfly genus Dicerapanorpa Zhong & Hua, 2013 is taxonomically reviewed. Two new species of Dicerapanorpa are described and illustrated, increasing the species number of this genus to 20. Dicerapanorpa bifurcata sp. nov. from the Minshan Mountains, Sichuan Province, is characterized by the absence of the paramere basal branch and the elongated mesal branch in males, and the medigynium having a short basal stalk in females. Dicerapanorpa zhengkuni sp. nov. from the Wuling and Miaoling Mountains, Guizhou Province, is distinguishable by the greatly elongated hypovalves, the very short basal branch of the paramere, and the dorsomedially curved lateral branch in males, and the rounded main plate of the medigynium in females. An updated key to species of Dicerapanorpa is presented.